Menumbuhkan Rasa Nasionalisme dan Patriotisme Pada Anak Sekolah Dasar Melalui Pembelajaran IPS - Gina Amalia; Auliadi Auliadi; Tin Rustini; Muh. Husen Arifin (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Many Indonesian citizens, including elementary school children, have been carried out by external developments due to increasing technological growth. They forget that the true identity of an Indonesian citizen is to love his own country. Therefore, more is needed to improve nationalism in Indonesia, which starts as early as at Sd through ips study. The education materials given are about Indonesia's independence process. At the first meeting before class, children are taught to pray before and after learning to create a religious consciousness so that children realize that in the Indonesian state, there is a variety of religions and a growing love for the Indonesian state. Additionally, there are methods given during learning that are contextual teaching and learning (TCL) and higher order thinking skill (hots). Contextual teaching and learning (TCL) is a system that links learning materials to daily life, such as taking the possible values of Indonesia's independence from hard work, cooperation, and foremost nationalism and patriotism. Then, there is called higher order thinking skill (hots) which is the method of discussion students perform about taking a meaning from the Indonesian independence event. With such a method, it will add to the student's knowledge and love of the country. In addition, students become proficient at thinking critical of the learning materials. As a result of this writing was the invention of several methods and ways that a teacher can promote nationalism in elementary school students by studying ips related materials for Indonesia's independence process. Not only teachers but parents also contribute greatly to the efforts of increasing nationalistic values in their children